ANALISIS PROSES MANUFAKTUR MESIN PENGIRIS PISANG MENGGUNAKAN METODE DESIGN FOR MANUFACTURE AND ASSEMBLY (DFMA) - M. Ghifari Naufal Irsan (2021)
The unaffordable price of banana slicing machines and the difficulty of manufacturing make it difficult for MSMEs (Micro, Small and Medium Enterprises) to have their own banana slicing machine and still rely on slicing bananas using a kitchen knife manually. Manual production has a weakness, namely limited production capacity. For this reason, the development of a banana slicing machine design needs to be done using the Design For Manufacture And Assembly (DFMA) method. The use of the DFMA method can reduce the number of components and difficulties during the manufacturing process. With DFMA, it is possible to compare the selected materials and manufacturing processes, determine the cost impact of these materials and processes so as to find the most efficient use of component designs and reduce production costs.